Microhabitat selection by macroinvertebrates: generality among rivers and functional interpretation. Issue 1 (15th March 2022) - Forcellini, M.; Plichard, L.; Dolédec, S.; Mérigoux, S.; Olivier, J.-M.; Cauvy-Fraunié, S.; Lamouroux, N.
Abstract: The transferability of hydraulic microhabitat selection models among rivers has been largely debated. It can influence management decisions such as restoration measures or environmental flow definitions. We updated microhabitat selection models for 258 macroinvertebrate taxa, with 141 species, collected in 2128 Surber or Hess samples during 91 surveys (sites × dates) distributed in eleven small streams to large rivers of Germany and France. We compared microhabitat selection for four hydraulic variables, developed using mixed-effects models that account for the overdispersion of observed abundance, partly due to spatial aggregation. Models based on bed shear stress, water column velocity and Froude number showed comparable results and were stronger than models for water depth. For these velocity-related variables, 61–78% of models were significant and revealed variable response forms among taxa. The explanatory power of "average" microhabitat selection models, with response forms common to all surveys, was 78–83% of the explanatory power of more detailed models with variable response forms. Significant associations with biological traits such as locomotion, relation to substrate or food types suggested that microhabitat selection results from general biological processes. Our results indicate a high degree of transferability and can be useful in many basic and applied ecological studies.